2006
DOI: 10.2139/ssrn.932511
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Costs in Ukraine

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This study is similar to the one conducted for Russia [5] and Ukraine [4]. These studies demonstrated how health risk analysis could be adapted and applied in the former Soviet Union, taking into account important factors such as data availability, demographics, and the composition of industrial emissions.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…This study is similar to the one conducted for Russia [5] and Ukraine [4]. These studies demonstrated how health risk analysis could be adapted and applied in the former Soviet Union, taking into account important factors such as data availability, demographics, and the composition of industrial emissions.…”
Section: Methodssupporting
confidence: 69%
“…Avaliani and Revich [8] proposed a 0.55 conversion coefficient to convert TSP into PM10 for Russia, slightly below the 0.6 conversion coefficient suggested in Larson et al [1] for Russia and in Strukova et al [4] for Ukraine. Many fo rmer Soviet regions have more combustionrelated activities than average, so using a higher coefficient to convert TSP to PM10 than the world average coefficient of 0.5 would be appropriate [5].…”
Section: Conversion Of Tsp To Pm10mentioning
confidence: 99%
“…Avaliani and Revich [14] proposed a 0.55 conversion coefficient to convert TSP into PM 10 for Russia. This value is slightly below the 0.6 conversion coefficient suggested in Larson et al [15] for Russia and Strukova et al [16] proposed for Ukraine. Because many former Soviet regions have more combustion-related activities than average, a higher conversion coefficient was used than that for the world average 0.5 [17].…”
Section: Resultsmentioning
confidence: 49%
“…A number of studies in the region conducted between 1996 and 2008 have estimated health risks from air pollution in Russia and Ukraine [3,4,6,7,16,26] or Kazakhstan [27] and have generally concluded that there are significant health risks from inhalation of pollutants, particularly particulate matter. Ambient air pollution standards in the former Soviet Union required short-term pollutant estimates for all major pollution sources.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate the implications of the IEVSL for cross-country benefit transfer, we present an example using parameters from a study by Strukova et al (2006) that estimates the mortality costs of air pollution in major Ukrainian cities. The lack of VSL estimates based on Ukrainian data necessitated the benefit transfer.…”
Section: Environmental Protection Agency's (Epa) Recently Revised Guimentioning
confidence: 99%